Result Culture & ROWE: The Key to High Performance - Bungaran Saing; Achmad Fauzi; Idel Eprianto (Dinasti International Journal of Education Management and Social Science, 2026)
This study examines how result culture and Results-Only Work Environment (ROWE) influence high performance through technological support, transformational leadership, and work maturity. Using Structural Equation Modelling (SEM) with data collected from employees of PT STO Telkom Bekasi (N = 60), this study finds that technological support plays a dominant and significant role in improving high performance (β = 0.77, p < 0.05). While result culture significantly influences transformational leadership and employee work maturity, it does not directly enhance high performance. Similarly, ROWE significantly improves technological support, which in turn enhances high performance. These findings suggest that cultural and work-environment reforms alone are insufficient without strong digital infrastructure support. The study contributes to the performance management literature by identifying technological support as a critical enabling mechanism in results-based work systems.